ANALISIS PROGRAM AUSBILDUNG: KERJASAMA INDONESIA-JERMAN DALAM UPAYA MENINGKATKAN TINGKAT PENDIDIKAN KEJURUAN (STUDI KASUS SMKN 6 MALANG) - Aditama, Wenda; Susanto, Kun Hery; Akhmad, Muhammad Rhosyid; Wibowo, Afa; Kurniawan, Prawidana; Pujakusuma, Dicky (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Abstract:Today's international market requires a lot of technical skills, so schools need to improve the quality of Indonesia's human resources. Therefore, Indonesia is focusing on developing vocational education and training. Indonesia has a wealth of resources but is not efficient, so it has a lot to learn from Germany. The result of this international cooperation is a training program (ausbildung). Using a qualitative method of document review and interviews with relevant sources, this article seeks to show how Indonesian-German cooperation in vocational education has impacted both countries. The article shows that the cooperation opens up new possibilities for intellectual Indonesians to earn a decent wage and be paid like professional workers in Germany